Situs Kota Tua di Batavia Situs Kota Tua di Batavia (1619-1942) Sebagai Bahan Ajar Mata Pelajaran Sejarah Peminatan: Situs Kota Tua di Batavia (1619-1942) Sebagai Bahan Ajar Mata Pelajaran Sejarah Peminatan - Kusuma, Hendra (Krinok: Jurnal Pendidikan Sejarah dan Sejarah, 2024)
Since the establishment of the city of Batavia by Jan Pieter Coen, who served as the Governor-General of the VOC since 1619, a city was founded and officially named Batavia in 1620. Batavia became a modern city and a center for trade, politics, governance, economy, and culture, and it was also one of the territories under Dutch East India Company control for approximately 300 years. In this writing, a qualitative descriptive research method is used with a literature study approach and steps to collect sources, as well as in the implementation of data collection and analysis procedures, four stages are undertaken, namely, data collection, reduction, presentation, and data verification. And based on the literature study that has been conducted, it can be concluded that teaching materials are materials containing detailed and integrated information about the subject matter. And based on the literature study that has been obtained, it can be concluded that teaching materials are materials containing detailed and integrated information about the subject matter used to carry out a learning process. Therefore, historical sites and information and data about the history of Batavia, or often known as Old Batavia, especially during the period of 1619-1942, can be used as references for the preparation or creation of teaching materials in the history subject, which is interesting to improve the success of the history learning process itself.